Authoritarian capitalism in the age of globalization / Peter Bloom. - Bloom, Peter (Social science teacher) (Edward Elgar Publishing, 2023)
Exploring the rise of authoritarian capitalism, this book offers a fresh perspective on politics and economics in the present age of globalisation. It asks the crucial question of whether individuals and nations can break free from the 'grip' of authoritarian capitalism in the 21st century.